2002
DOI: 10.1515/cclm.2002.231
|View full text |Cite
|
Sign up to set email alerts
|

The Prognostic Value of Nutritional and Inflammatory Indices in Critically Ill Patients with Acute Respiratory Failure

Abstract: In critically ill patients suffering from acute respiratory failure, weaning from ventilatory assistance is a key survival factor in intensive care units (ICU). The aim of this study was to provide deeper insight into laboratory methods allowing improved monitoring of that critical period. Eighty-three ICU patients (mean age 63.9 years), classified according to the Second Acute Physiology and Chronic Health Evaluation criteria, were submitted to mechanical ventilation, antibiotherapy and nutritional support. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 17 publications
0
17
0
1
Order By: Relevance
“…16 Initial studies in acutely ill ICU and trauma patients have found the PINI served as an accurate predictor of clinical outcomes. 18,19 In chronic renal failure patients receiving hemodialysis, increased PINI levels are associated with malnutrition and increased risk of comorbidites. 20 Cancer patients have significantly elevated PINI levels, and measurement of serial PINI levels has been proposed to assess overall nutrition and prognosis in this population.…”
Section: Discussionmentioning
confidence: 99%
“…16 Initial studies in acutely ill ICU and trauma patients have found the PINI served as an accurate predictor of clinical outcomes. 18,19 In chronic renal failure patients receiving hemodialysis, increased PINI levels are associated with malnutrition and increased risk of comorbidites. 20 Cancer patients have significantly elevated PINI levels, and measurement of serial PINI levels has been proposed to assess overall nutrition and prognosis in this population.…”
Section: Discussionmentioning
confidence: 99%
“…The multimeric form of plasma transthyretin, on the contrary, showed an increase in SARS. Transthyretin has been shown to be a valuable prognostic factor of nutritional and inflammatory indices in patients with acute respiratory failure (34). A persistent low level of serum transthyretin is predictive of lethality, whereas increased levels were associated with improved ventilatory performances.…”
Section: Discussionmentioning
confidence: 99%
“…Inflammatory (C-reactive protein and a 1 -acid glycoprotein) and nutritional risk (serum albumin and transthyretin) parameters, as measured by the Prognostic Inflammatory and Nutritional Index (PINI), have been associated with outcomes in hospitalized patients [37]. Schlossmacher et al [38] found that the PINI scoring formula worked as an independent predictor of the respirator weaning trial outcome. Longer weaning time is associated with an increased length of hospital stay.…”
Section: Biochemical Parametersmentioning
confidence: 99%